Effect of Sodium Hydroxide on Geotechnical Properties of Soft Soil in Kathmandu Valley - Yadav, Suresh Ray; Sharma, Bal Deep; Malla, Birasa (Academic Journal of Simara, 2026)
People utilize local soils a lot in building because they are easy to get and cheap, but they don’t last long enough for most uses. To overcome this constraint, this study assesses the efficacy of mineral polymerization (MIP) utilizing sodium hydroxide (NaOH) as a stabilizing agent for black organic silt soil. The soil examined, prevalent in the Kathmandu Valley, is of lacustrine origin, distinguished by elevated organic content and diminished strength. testing in the lab included testing for grain size distribution, Atterberg limits, organic content, and pH. We did unconfined compressive strength (UCS) tests on samples that were stabilized with different amounts of NaOH and sand as a filler at the best moisture content. Tests were done on samples in dry, rainy, and wet-dry cycling conditions. The highest UCS values were 77.57 kg/cm2 for dry conditions, 38.85 kg/cm2 for wet conditions, and 56.30 kg/cm2 for cycling conditions. For untreated soil, the highest value was 7.38 kg/cm2. The lowest strengths of treated wet and cycling specimens were nevertheless higher than those of the natural soil. The results show that MIP based on NaOH makes soil much stronger and more durable, which suggests that it could be used sustainably in building.